2023
DOI: 10.3389/fpls.2023.1132861
|View full text |Cite
|
Sign up to set email alerts
|

Different leafy vegetable cropping systems regulate growth, photosynthesis, and PSII functioning in mono-cropped eggplant by altering chemical properties and upregulating the antioxidant system

Abstract: Continuous cropping of eggplant threatened regional ecological sustainability by facilitating replanting problems under mono-cropping conditions. Therefore, alternative agronomic and management practices are required to improve crop productivity at low environmental cost for the development of sustainable agricultural systems in different regions. This study examined changes in soil chemical properties, eggplant photosynthesis, and antioxidant functioning in five different vegetable cropping systems over a 2-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…This study found that CC has been observed to reduce the F v /F m , F v /F 0 , and F m /F 0 in P. odoratum. Consistent with this current study's findings, previous research on vegetables showed that F v /F m values were substantially affected by various leafy vegetable cropping systems [25].…”
Section: Discussionsupporting
confidence: 92%
“…This study found that CC has been observed to reduce the F v /F m , F v /F 0 , and F m /F 0 in P. odoratum. Consistent with this current study's findings, previous research on vegetables showed that F v /F m values were substantially affected by various leafy vegetable cropping systems [25].…”
Section: Discussionsupporting
confidence: 92%
“…The first group is edible mushrooms, the second group is protein-based nanoparticles, the third group is nano-nutrients, and the last group is Integrated farming practices are a critical tool for achieving sustainable farming and should be adopted. These practices may include no-tillage farming [72], crop rotations [73,74], and crop-livestock mixed systems [75], among others [76]. Sustainable farming cannot exist using only a single approach, as integrated and systematic technologies are needed to overcome the negative effects of single practices and avoid unhealthy and imbalanced effects on agro-ecosystems [61].…”
Section: Nano-food Farming: An Overviewmentioning
confidence: 99%
“…Therefore, through reasonable crop rotation and stubble planting, the soil environment can maintain a stable microbial abundance and soil enzyme activity level, and it is possible to increase soil fertility, maintain the nutrient balance, and promote sustainable productivity. The appropriate planting system can promote crop growth and development [20,21].…”
Section: Introductionmentioning
confidence: 99%